PENGGUNAAN TEKNOLOGI GAMIFIKASI PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Sundahry; Yantoro (Jurnal Muara Pendidikan, 2025)
The purpose of this study is to conduct a systematic literature review (SLR) on the utilization of gamification technology in primary school science learning. Gamification is a learning method that integrates game elements to increase student engagement in the learning process. In this study, researchers analyzed papers published between 2020 and 2024 that focused on the application of gamification in primary education. The research shows that gamification is effective in creating an interactive and fun learning environment and can increase students' science learning motivation. The method also helps teachers present material in a way that is more interesting and easy for students to understand. Therefore, the use of gamification in science learning not only improves learning outcomes but also encourages students to actively participate in the learning process. This study recommends that teachers consider using gamification as an innovative teaching strategy to achieve more optimal learning outcomes.